Major satellite repeat RNA stabilize heterochromatin retention of Suv39h enzymes by RNA-nucleosome association and RNA:DNA hybrid formation - Velazquez Camacho, Oscar; Galan, Carmen; Swist-Rosowska, Kalina; Ching, Reagan; Gamalinda, Michael; Karabiber, Fethullah; De La Rosa-Velazquez, Inti; Engist, Bettina; Koschorz, Birgit; Shukeir, Nicholas; Onishi-Seebacher, Megumi; van de Nobelen, Suzanne; et al. (eLife, 2017)
The Suv39h1 and Suv39h2 histone lysine methyltransferases are hallmark enzymes at mammalian heterochromatin. We show here that the mouse Suv39h2 enzyme differs from Suv39h1 by containing an N-terminal basic domain that facilitates retention at mitotic chromatin and provides an additional affinity for major satellite repeat RNA. To analyze an RNA-dependent interaction with chromatin, we purified native nucleosomes from mouse ES cells and detect that Suv39h1 and Suv39h2 exclusively associate with poly-nucleosomes. This association was attenuated upon RNaseH incubation and entirely lost upon RNaseA digestion of native chromatin. Major satellite repeat transcripts remain chromatin-associated and have a secondary structure that favors RNA:DNA hybrid formation. Together, these data reveal an RNA-mediated mechanism for the stable chromatin interaction of the Suv39h KMT and suggest a function for major satellite non-coding RNA in the organization of an RNA-nucleosome scaffold as the underlying structure of mouse heterochromatin.
Keywords: Suv39h1; Suv39h2; major satellite repeat; pericentric heterochromatin; non-coding RNA; RNA:DNA hybrids